MONITORING OF DEGRADATION PROCESS OF THE SHORE DEFENCEWORKS IN ERODABLE RIVERBEDS (PANGEEA, 2025)
The paper presents the results of the research on the monitoring of the degradation of the shore defence works located in the Moldova riverbed, in the area of Soci, Iaşi County. In the research area there are located three potable water pipelines that undercrossing the river Moldova. Monitoring was carried out by performing topographical measurements at predetermined time intervals as well as following hydrological risk events. Topographic measurements have been materialized by realizing topographical plans for the study area, transverse profiles and longitudinal profiles through the riverbed. The processing of topographic plans and cross-sections has resulted in the degradation of shore defence works under the influence of natural and anthropogenic risk factors. The analysis of the cross-sectional profiles indicated the hydrodynamic erosion over time of shore defence works. The analysis of the longitudinal profiles indicated the process of deepening the riverbed of the Moldova River on the researched section. The results of the research have allowed the design of river bedside and shore defence in the study area.